Portrait of Observing, Inferring, and Predicting Skills of Junior High School Students - Pratiwi Mega Lestari; Edi Istiyono (Jurnal Penelitian Pendidikan IPA, 2025)
The goal of science learning is achieved when students master key skills: observing, inferring, and predicting. Field studies indicate that teachers face challenges in comprehensively assessing these skills. This study aims to portray the observing, inferring, and predicting skills of junior high school students in Tanjungpinang. A quantitative descriptive method was employed, with a target population of eighth-grade students from state junior high schools in Tanjungpinang. Stratified random sampling based on school accreditation levels resulted in a sample of 208 students. Data collection involved a test on work and simple machines material, which was analyzed using descriptive statistics. The findings reveal that the average interval scores for observing, inferring, and predicting skills were 13.52, 5.49, and 1.93, respectively, placing them in the medium category, indicating potential for further development. These results highlight the need for targeted quality improvement programs and increased resource support to enhance science learning. Implementing diverse strategies and innovations in science teaching materials is essential to improve these skills.